Nurses’ Spiritual Well-Being and Spiritual Care Competence: A Cross-Sectional Study in Indonesia - Bella Davista Sitorus; Desniwati Laoli; Juniarta Juniarta; Komilie Situmorang (Nursing Current: Jurnal Keperawatan, 2025)
Spiritual well-being is a dynamic state wherein individuals may perceive and articulate affirmative emotions, actions, and thoughts in their interactions with themselves, others, the environment, and the transcendence (God). Aimed to analyze the relationship between nurses' spirituality and their competence in providing spiritual care to patients, the study employed a quantitative correlational method and a cross-sectional research design, selecting a sample of 348 Indonesian nurses who were actively working in various care units in hospitals or health centres. Spiritual Well-Being Scale (SWBS) (Cronbach's Alpha = 0.904) was utilized to measure nurses' spirituality, and the Spiritual Care Competency Scale (SCCS) (Cronbach's Alpha = 0.962) was employed to measure nurses’ spiritual care competence. A Spearman correlation was conducted to evaluate the relationship between nurses’ spiritual well-being and nurses’ spiritual care competence. There was a significant positive relationship between the two variables, rs (356) = 0.214, p < 0.001. The results indicated that spiritual well-being can enhance nurses’ ability to provide spiritual care. Further research can address the limitations and shortcomings of the current study to provide respondents with a more comprehensive understanding of the relationship between spiritual well-being and nurses' spiritual care competence. Additionally, future research can explore the various factors that influence both spiritual well-being and spiritual care competence.